Estimation of Carbon Emission (CO2) as Forest and Land Fire impact at various Land Cover Types in Riau Province during year 2000-2009 - Bambang Hero Saharjo; Erianto Indra Putra; Renando Meiko Putra (Jurnal Silvikultur Tropika, 2013)
Forest and land fire is one of the most disturbance form that can decrease area and forest function. Forest and land fire is often connected with conversion activity, from forest area to non-forest area. Conversion activities significantly increase because of the increasing of human need on the land. Riau is one of province that vulnerable to the forest and land fire, Based on recorded data it had been found that in the on year 2005 burned area in Riau was about 24,500 ha. One of the important factors which cause forest and land fire in Riau province is conversion activitye. Hotspot can be use as one indicator to determining vulnerability of forest and land fire. Negative impact that occured from forest and land fire is connected with carbon emission. The research aims to analyze the occurance of forest and land fire at various land cover type during 2000-2009 and also the estimation of produced carbon emissions.Keywords: carbon emission, hotspot, land cover